The mineralogy and genesis of the lead-zinc-vanadium deposit of Abenab West in the Otavi mountains, South West Africa - Verwoerd, W. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1953.